REALISME MAGIS DALAM NOVEL THE CHRONICLES OF NARNIA: THE MAGICIAN'S NEPHEW KARYA C. S. LEWIS - Azzahra Diva Daloca; Martono; Ahmad Rabiul Muzammil (STKIP Subang, 2026)
This research aims to analyze magical realism in the novel The Chronicles of Narnia: The Magician’s Nephew by C. S. Lewis. The method used to analyze the data in this study is a descriptive method with a qualitative research form. The data source analyzed in this research is the novel The Chronicles of Narnia: The Magician’s Nephew by C. S. Lewis. The data in this study consists of quotes or sentences in the novel that contain characteristics of magical realism, including irreducible element, phenomenal world, unsettling doubts, merging realms, and disruptions of time, space, and identity. The theory used as the main reference in this research is the theory of magical realism by Wendy B. Faris. The results of this study show that in the novel The Chronicles of Narnia: The Magician’s Nephew by C. S. Lewis, there are characteristics of magical realism in the form of an unreduced element consisting of magical characters, magical sounds, and magical events, a phenomenal world in the form of places or locations that exist in the real world, the unsettling doubt of the characters, the unification of the magical and the real in the form of objects, and also the disruption of time, space, and identity. Based on these five characteristics, the dominant data results in this study are the characteristics of the unreduced elements with indicators of magical events categorized into teleportation events, the characters' magic, and the magically formed new world called Narnia.